Christians and Nationalism in India: A Theological Engagement in Public Sphere - Wilson, Viju (International journal of public theology, 2025)
Nationalism in India has become a highly sensitive issue, particularly in the context of its diverse, multi-religious population. Religious nationalist ideologies have sought to define the nation, citizenship, and loyalty based on religious identity, challenging the secular nationalist ideals that once united Indians in their struggle against colonial rule. This article argues that Christians cannot support any form of nationalism that excludes fellow citizens on the grounds of religion or ethnicity, as such exclusivist rhetoric is fundamentally incompatible with Christian teachings. Nationalist ideologies that promote exclusivism are inherently detrimental to national cohesion, as they hinder the process of nation-building. In India, religious nationalism - especially the Hindutva ideology cloaked in cultural terms - represents a divisive and sectarian agenda. In contrast, true Indian nationalism is inclusive, embracing all citizens, regardless of their cultural or religious backgrounds.